Impact of HbA1c, Blood Pressure, and Cholesterol on Ocular Complications in Type 2 Diabetes Mellitus: A Clinical Analytical Study from Libya - Marai A.Mohamed El-khajkhaj; Ebtisam Elgazwi; Esraa Alshary; Miami Al-Mzaini (African Journal of Advanced Pure and Applied Sciences, 2025)
Type 2 Diabetes Mellitus (T2DM) is a major chronic condition globally and increasingly prevalent in Libya. Among its systemic complications, ocular disorders such as cataract, retinal detachment, and internal retinal hemorrhage pose significant risks to vision. This study evaluated the association between HbA1c, blood pressure (BP), and cholesterol levels with diabetic eye complications in Libyan patients. Data were obtained via electronic surveys distributed through the Libyan Diabetes Association and supplemented with clinical records from endocrinology centers. Patients were categorized into groups with and without retinopathy, including specific subtypes. Laboratory measurements were conducted using standardized devices (Mindray BS-240, Hemo One ISE). The findings revealed a strong association between elevated HbA1c (≥9%), high BP (>160/90 mmHg), and serum cholesterol (>200 mg/dL) with the occurrence of ocular complications. Cataract cases showed progressive metabolic deterioration, while retinal detachment and internal hemorrhage were more pronounced in those with combined dysregulation. Interestingly, patients without eye complications maintained stable metabolic parameters, highlighting the protective effect of early and integrated control. Gender-based differences in internal hemorrhage suggested possible physiological influences beyond chronic markers. The results reinforce the need for comprehensive diabetic care models incorporating glycemic, cardiovascular, and lipid monitoring. Community organizations like the Libyan Diabetes Association play a key role in data collection, patient education, and screening. The study advocates for multi-specialty collaboration and the implementation of national preventive frameworks to reduce diabetes-related visual loss.